North Atlantic Natural Variability Modulates Emergence of Widespread Greenland Melt in a Warming Climate. Issue 17 (10th September 2018) - Hahn, L.; Ummenhofer, C. C.; Kwon, Y.‐O.
Abstract: Record‐breaking melt over Greenland in recent decades is linked not only to climate change but also to natural variability, including persistent atmospheric high‐pressure conditions in the negative phase of the North Atlantic Oscillation and warm North Atlantic Ocean temperatures during the positive phase of the Atlantic Multidecadal Oscillation. However, the relative importance of natural variability for Greenland melt under varying degrees of greenhouse forcing is still unclear. Using reanalysis data and a large ensemble of climate model simulations, we find that a negative North Atlantic Oscillation and positive Atlantic Multidecadal Oscillation consistently promote heightened summer melt under various forcing conditions. Moreover, timing of widespread 21st century Greenland melt varies considerably between ensemble members due to different phasing of these modes of natural variability. These results indicate the importance of natural modes of variability across a range of external forcing conditions for interannual melt variability and the emergence of widespread Greenland melt. Plain Language Summary: Extreme Greenland Ice Sheet melt is partly driven by climate change, as rising greenhouse gas concentrations promote warmer temperatures, especially for the Arctic region. However, natural fluctuations in the climate system can also promote Greenland melt. In particular, persistent high‐pressure systems in the atmosphere over the region and warm North Atlantic Ocean temperatures have been linked to enhanced Greenland melt in recent decades. Yet the importance of these natural oscillations for melt in the past and future remains unclear. We use a series of climate model simulations to show that high‐pressure conditions and a warm North Atlantic Ocean consistently promote heightened summer melt under various warming scenarios for the past and future. Additionally, the timing of widespread Greenland melt in the 21st century depends on the timing of these modes of natural variability. Key Points: Links between natural variability and Greenland melt are studied under various greenhouse forcings in the Community Earth System Model A negative summer North Atlantic Oscillation and positive Atlantic Multidecadal Oscillation promote extreme melt in all forcing scenarios The timing of emergence of widespread 21st century Greenland melt is dependent on the phasing of these modes of natural variability